(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Analysis of the frequency of referrals to the outpatient network in our country has shown that from 40 to 70% of patients in polyclinics come to the doctor complaining of pain, with the most common being back pain. Depending on the causes of back pain is divided into specific and nonspecific. Non-specific character of back pain is observed in 90% of cases. The frequency of specific back pain does not exceed 8-10%, compression radiculopathy of the lumbosacral roots is observed in no more than 3-5% of patients with back pain.